2016
DOI: 10.1016/j.jtho.2015.12.097
|View full text |Cite
|
Sign up to set email alerts
|

A Case of ALK-Rearranged Adenocarcinoma with Small Cell Carcinoma-Like Transformation and Resistance to Crizotinib

Abstract: Histologic changes can be involved in resistance to anticancer drugs. Transformation to small cell lung carcinoma (SCLC) following treatment with EGFR tyrosine kinase inhibitors has been reported in patients with EGFR-mutant lung adenocarcinoma. Herein, we report a case of ALK-rearranged lung adenocarcinoma with SCLC-like histology in a metastatic abdominal nodule that was resistant to crizotinib therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 5 publications
1
39
1
Order By: Relevance
“…Preclinical studies have also suggested that EMT is associated with resistance to crizotinib and ceritinib (43)(44)(45), but clinical specimens were not examined in these reports. Of note, other phenotypic changes, such as transformation to SCLC, have been shown to mediate resistance in EGFR-mutant lung cancer and rarely in ALK-positive NSCLC (36,(46)(47)(48). However, we did not observe transformation to SCLC in any specimens in this series.…”
Section: Discussioncontrasting
confidence: 65%
“…Preclinical studies have also suggested that EMT is associated with resistance to crizotinib and ceritinib (43)(44)(45), but clinical specimens were not examined in these reports. Of note, other phenotypic changes, such as transformation to SCLC, have been shown to mediate resistance in EGFR-mutant lung cancer and rarely in ALK-positive NSCLC (36,(46)(47)(48). However, we did not observe transformation to SCLC in any specimens in this series.…”
Section: Discussioncontrasting
confidence: 65%
“…With respect to EGFR-TKIs, 3%–15% of the patients with EGFR -mutated lung cancer develop acquired resistance to EGFR-TKIs by histologic transformation to SCLC 15,16. Similarly, a mechanism underlying SCLC transformation in ALK -positive tumors has been reported in some cases 612…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, histological transformation from adenocarcinoma to SCLC has been reported in several ALK‐TKI‐refractory cases, such as alectinib‐resistant cases. Similar to the SCLC transformation, which is well‐known in EGFR‐TKI‐resistant cases, classic cytotoxic chemotherapy is thought to be effective for overcoming resistance …”
Section: Mechanisms Of Alk‐tki Resistancementioning
confidence: 99%
“…Similar to the SCLC transformation, which is well-known in EGFR-TKI-resistant cases, classic cytotoxic chemotherapy is thought to be effective for overcoming resistance. 73,74 3.3 | Challenges for the future Currently, multiple ALK-TKIs (three in Japan and 4 in the USA) have been approved and are used clinically. In Japan, all three ALK-TKIs have been approved as first-line therapies for ALK-rearranged NSCLC.…”
Section: Bypass Pathway or Other Mechanismmediated Resistancementioning
confidence: 99%